Inspire technology center - Rodriguez, Johanan A.; Araneta, Maureen Anne L. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
In this present date and age, the development of technology is advancing at such a rapid pace. This constant innovation is brought about by people coming together to have a conversation with regards to technology, and how it can be made better. The design thesis will provide, a venue for the promotion of these conversations. With all the ideas, experiences, and even theories, that different people, such as the general public, students, businessmen inventors, and the like have, providing a venue for interest and interaction between these people would promote an environment of conversation, the drive the evolution of technology even further into the future. This is also where concepts of cognitive surplus, that drive people from being mere consumers into collaborators, comes into play. The design thesis will provide a venue for this to occur and in the process create the chance encounter that eventually creates conversation. These different processes and concepts were put together in the form of a building with museums, exhibit halls, discussion rooms, auditoriums, and others. These spaces were also designed with concepts of, adaptability, flexibility, and the promotion of conversation in mind. All of which would make up the "Inspire: Technology Center."
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Technology center